PENGARUH METODE PEMANASAN DALAM OVEN DAN REFLUKS PADA SINTESIS ZEOLIT ZSM-5 DARI LIMBAH AMPAS TEBU - ., Ngadiyono; ,S.Si, M.Si, Sriatun; ,M.Si, Dra. Taslimah (Chem Info Journal, 2013)
The synthesis of ZSM-5 was done from bagasse waste ash and sodium silicate as source of silica and aluminium hydroxide as source of alumina with use heating method on oven and reflux. The synthesis was done by reacting sodium silicate and sodium aluminate at pH 11-12 until is formed gel. Gel through are taken to caried out heating on oven and reflux at 1100C for 1, 3, 5, dan 7 days. Product which obtained are washed by aquades until pH neutral, through are dried at 1100C for 10 hours.Characterization of product are carried out by Fourrier Transform InfraRed (FTIR) and X-Ray Diffraction (X-RD). Heating use reflux more effective than oven. Optimum result are obtained for heating at 5 days. Diffractogram are obtained showed that mixture of mineral such as Nacrite, Aluminum Silicate Oxide Hydrate, and ZSM-5. Spectrum FTIR showed that heating on reflux at wavenumber 609,51 cm-1 are showed double ring vibration of ZSM-5 framework.